Relationship between knowledge and adherence to hypertension treatment - Liza Pristianty, - (PagePress Publications, 2022)
Background: Hypertension is a continuous increase in arterial blood pressure. About 50-70% of patients do not comply with hypertension treatment. Adherence is a health behavior that can be influenced by several factors, including knowledge.